Regulation of NAMPT in Human Gingival Fibroblasts and Biopsies. (24th February 2014) - Damanaki, Anna; Nokhbehsaim, Marjan; Eick, Sigrun; Götz, Werner; Winter, Jochen; Wahl, Gerhard; Jäger, Andreas; Jepsen, Søren; Deschner, James
Abstract : Adipokines, such as nicotinamide phosphoribosyltransferase (NAMPT), are molecules, which are produced in adipose tissue. Recent studies suggest that NAMPT might also be produced in the tooth-supporting tissues, that is, periodontium, which also includes the gingiva. The aim of this study was to examine if and under what conditions NAMPT is produced in gingival fibroblasts and biopsies from healthy and inflamed gingiva. Gingival fibroblasts produced constitutively NAMPT, and this synthesis was significantly increased by interleukin-1 β and the oral bacteria P. gingivalis and F. nucleatum . Inhibition of the MEK1/2 and NF κ B pathways abrogated the stimulatory effects of F. nucleatum on NAMPT. Furthermore, the expression and protein levels of NAMPT were significantly enhanced in gingival biopsies from patients with periodontitis, a chronic inflammatory infectious disease of the periodontium, as compared to gingiva from periodontally healthy individuals. In summary, the present study provides original evidence that gingival fibroblasts produce NAMPT and that this synthesis is increased under inflammatory and infectious conditions. Local synthesis of NAMPT in the inflamed gingiva may contribute to the enhanced gingival and serum levels of NAMPT, as observed in periodontitis patients. Moreover, local production of NAMPT by gingival fibroblasts may represent a possible mechanism whereby periodontitis may impact on systemic diseases.